Stratigraphy of the synorogenic Cenozoic volcanic rocks of Cajamarca and Santiago de Chuco, northern Peru - Navarro Colque, Pedro Alexis (2008)
Cenozoic volcanic deposits that cap the Western Cordillera of Northern Peru originally were mapped as one unit called “Volcánicos Calipuy” by Cossío (1964). Later studies (Reyes, 1980; Cobbing, 1981; Wilson, 1984) used the name Calipuy Group including within it several volcanic sequences with local informal names as “Volcánicos Llama, Porculla, Huambos, Chilete and Tembladera”. Nevertheless, Hollister & Sirvas (1978) were the first in establish an association between those volcanic deposits and processes like volcanoes growth and explosive activity. Facies interpretation, updated mapping and volcanic stratigraphy allow the recognition of three segments (Figure 1) constituted by volcanic rocks of Cenozoic age in northern Peru: Huancabamba (4º - 6º S), Cajamarca (6º - 7º 30’ S) and Santiago de Chuco (7º 30’ – 9º S), all them emplaced between Eocene and upper Miocene from 54.8 ± 1.8 to 8.2 ± 0.2 Ma (Noble et al., 1990; Turner, 1997; Davies, 2002; Noble & Loayza, 2004; Noble et al., 2004; Longo, 2005; Rivera et al., 2005). So that, these volcanic rocks overlies unconformably carbonated and clastic sequences from Mesozoic time. The volcanic activity was characterized by intense and continuous explosive and effusive phases that emplaced thick pyroclastic and lava flow deposits corresponding to five volcanic stages from early Eocene, upper Eocene, Oligocene, early Miocene to upper Miocene, suggesting a continuity in the emplacement and eastward migration of the magmatic arc during approximately 46 Ma. Mainly the volcanic centres show a trend NW-SE, similar with regional faults and trending fractures. This paper shows geological cartography, regional structural setting and stratigraphy results carried out only in Santiago de Chuco and Cajamarca segments.